PENGARUH STRUKTUR MODAL, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP KEPUTUSAN INVESTASI (Studi Kasus Pada Sektor Industri Barang Konsumsi Perusahaan Makanan Dan Minuman Yang Terdaftar DI Bursa Efek Indonesia Periode 2012-2016) - Rosmah Sholichah; Ronny Malavia Mardani; Muhammad Agus Salim (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTConducting the research it has several aims as follows: (1) To find out theeffect of Modal Structure toward taking the investment decision throughConsumer Good sub sector of food and Beverage Company, (2) to find out theeffect of profitability of taking the investment decision through Consumer Goodbusiness of sub sector of food and Beverage Company, (3) finding the effect ofcompany dimension of taking the investment decision through the Consumer Goodbusiness of sub sector of food and beverage company.The population of research includes all the food and beverage company that wasnoted at the Bursa Efek Indonesia (BEI) on period 2012 – 2016. Duringconducting this research it use the purposive sampling as the sample selection.According to the criteria that led the research, there are 11 companies used as thesample of research. The method that will be used is regression linear bifilar as themethodology of research.Based on the result of this research, it can be point out into several conclusionssuch as: 1)The result of the t-test shows that modal of structure variable does nothave significantly impact on the investment decision. It reveals that the significantscore occurred by the structure of modal on 0,05 is 0,156. 2) The result of the ttest from profitability variable also shows that it does not have any significanteffect for the investment decision. This fact reveals that the significant scoreobtained the profitability on 0,05 is upper in 0,813. 3) The variable dimension ofthe company gives the significant impact toward investment decision; whereas itmeans that the significant score of variable size company under 0,05 is 0,04.Keywords: Structure of Modal, Profitability, Dimension of Company, andInvestment Decision